Patterns of data modeling - Blaha, Michael (Boca Raton, Florida : CRC Press, 2010)
""...should be on the shelf of every database, software, and systems architect. The book captures decades of experience, presenting distilled knowledge in a concise and easy-to-understand format. The breadth of coverage is enormous, ranging from basic data structures through star schema, archetypes for representing commonly found concepts, and canonical models for tough problems."---Paul C. Brown, Principal Software Architect, TIBCO Software Inc." ""... a clear book with precise definitions and excellent examples. All examples are presented in a graphical form that is easy to read and understand. Blaha assumes the reader has a basic understanding of data modeling, but gives his examples in such a way that if the reader needs some review, it is built in."---Toby Teorey, author of Database Modeling and Design, Fourth Edition" "Best-selling author and database expert with more than 25 years of experience modeling application and enterprise data, Dr. Michael Blaha provides tried and tested data model patterns to help readers avoid common modeling mistakes and unnecessary frustration on their way to building effective data models. Unlike the typical methodology book, Patterns of Data Modeling provides advanced techniques for those who have mastered the basics." "Focusing on databases rather than programming, this is one of the first books to apply the popular patterns perspective to database systems and data models. Dr. Blaha offers practical advice on the core aspects of applications and provides authoritative coverage of mathematical templates, antipatterns, archetypes, identity, canonical models, and relational database design."--BOOK JACKET
1. Mathematical templates -- 2. Summary of templates -- 3. Archetypes -- 4. Identity -- 5. Canonical models
Includes bibliographical references and index
Keywords: Data structures (Computer science); Databases; Software patterns